Multiscale Simulation of Protein Mediated Membrane Remodeling - Ayton, Gary S. (2009)
Proteins interacting with membranes can result in substantial membrane deformations and curvatures. This effect is known in its broadest terms as membrane remodeling. This review article will survey current multiscale simulation methodologies that have been employed to examine protein-mediated membrane remodeling.